Disability Level of Leprosy Patients in Ambon City, Maluku: A Retrospective Study from Eastern Indonesia - Pangestu, Juan Felix; Manuputty, Amanda Gracia; Asmin, Elpira; Tanamal, Rita; Titaley, Christiana Rialine; Tahitu, Ritha; Bandjar, Fitri Kadarsih (Berkala Ilmu Kesehatan Kulit dan Kelamin, 2023)
Background: Leprosy, also known as Hansen's disease, is a chronic endemic disease. The Corona Virus Disease 2019 (COVID-19) pandemic disrupted the implementation of the Neglected Tropical Diseases (NTDs) program such as the leprosy new case detection program. Leprosy is one of the chronic diseases that causes various problems due to the disability it causes. Purpose: To know the prevalence of leprosy and disability in 2018-2022 in Ambon City, Maluku, Indonesia. Methods: This research is a type of retrospective descriptive research whose aim is to find out the  epidemiology of leprosy patients in Ambon City, Maluku, Indonesia with a sample of were 131 people from 2018 to 2022. Result: The prevalence of disability levels 0 and 2 has the highest percentage in the 5-year span, occurring in 2019. However, during the COVID -19 pandemic, cases of level 1 disability tend to rise. Conclusion: Leprosy patients who had disability were more common  than those who had a disability.